Prevalence of Urinary Tract Infections and Antibiotic Susceptibility Patterns of Uropathogens among Neonates in Maternity Hospital, Kuwait: A Six-Year Retrospective Study - Moghnia, Ola H.; Al Otaibi, Hessah S.; Al Haqqan, Aisha M.; Sokhn, Elie S.; Pathan, Seema S.; Abdulaziz, Nawar E.; Mohammed, Habiba Y.; Al-Sweih, Noura A. (Medical principles and practice, 2025)
AbstractObjective: Urinary tract infections (UTIs) are common in neonates. Understanding the changes in the prevalence of common uropathogens is essential for early diagnosis and effective treatment of UTIs. This study aimed to identify etiological agents and determine the local antibiotic susceptibility patterns of uropathogens causing UTIs. Subjects and Methods: A retrospective cross-sectional descriptive study from January 2017 to December 2022 was conducted on hospitalized neonates at Maternity Hospital, Kuwait. Urine samples from neonates were analyzed to identify isolates, and antimicrobial susceptibility testing was determined using the VITEK® 2 system. Results: Out of 3,996 urine samples processed, 282 (7%) samples yielded significant bacteriuria, mostly from male 185 (65.6%). Gram-negative isolates were the most common 141 (50%), followed by yeasts 84 (29.8%) and Gram-positive isolates 57 (20.2%). The common uropathogens were Klebsiella pneumoniae 50 (17.7%), followed by Escherichia coli 47 (16.8%), Candida albicans 39 (13.8%), Enterococcus faecalis 34 (12%), and Staphylococcus epidermidis 17 (6%). High resistance rates were observed among Enterobacterales against ampicillin, cephalothin, cefuroxime, cefotaxime, nitrofurantoin, amoxicillin-clavulanic acid, ceftazidime, and trimethoprim-sulfamethoxazole. A total of 28 (56%) K. pneumoniae and 18 (38.3%) E. coli were extended-spectrum beta-lactamase producers. Conclusion: Gram-negative isolates are considered the predominant causative agents of UTIs in neonates at Maternity Hospital. Reduced antibiotic susceptibility to commonly used antibiotics poses a notable challenge in the clinical management of neonates with UTIs. This study underscores the importance of proactive surveillance in monitoring causative organisms and antibiotic susceptibility in neonates.